Structural characterization of a Δ3, Δ2-enoyl-CoA isomerase from Pseudomonas aeruginosa: implications for its involvement in unsaturated fatty acid metabolism. Issue 10 (3rd July 2019) - Liu, Li; Li, Tao; Peng, Cui-Ting; Sun, Chang-Zhen; Li, Chang-Cheng; Xiao, Qing-Jie; He, Li-Hui; Wang, Ning-Yu; Song, Ying-Jie; Zhu, Yi-Bo; Li, Hong; Kang, Mei; et al.
Abstract: Gene PA4980 from Pseudomonas aeruginosa encodes a putative enoyl-coenzyme A hydratase/isomerase that is associated with the function of the biofilm dispersion-inducing signal molecule cis -2-decenoic acid. To elucidate the role of PA4980 in cis -2-decenoic acid biosynthesis, we reported the crystal structure of its protein product at 2.39 Å. The structural analysis and substrate binding prediction suggest that it acts as a monofunctional enoyl-coenzyme A isomerase, implicating an alternative pathway of the cis -2-decenoic acid synthesis.